Ukraińskie dzieci w polskiej szkole. Perspektywa nauczycieli-wychowawców pracujących w świetlicy szkolnej = Ukrainian children in a Polish school. The perspective of teachers-educators working in a school common room - Grabarek, Katarzyna; Malon, Joanna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the article is to present the educational situation of children from different cultures in a Polish school and the teaching staff who face new, previously unknown tasks. Attention is drawn to the special role of the school common room as a place designed to perform the caring and integrating functions of a school.
Keywords: foreign children; migrations; multiculturalism; school common room; school; dzieci cudzoziemskie; migracje; wielokulturowość; szkoła; świetlica szkolna